Hydrochlorothiazide Use and Risk of Nonmelanoma Skin Cancers: A Biological Plausibility Study. (16th August 2021) - Bigagli, Elisabetta; Cinci, Lorenzo; D'Ambrosio, Mario; Nardini, Patrizia; Portelli, Francesca; Colucci, Roberta; Lodovici, Maura; Mugelli, Alessandro; Luceri, Cristina
Abstract : Recent studies reported the association between increased risk of nonmelanoma skin cancers (NMSCs) and the use of hydrochlorothiazide (HCTZ), one of the most commonly prescribed diuretic, antihypertensive drug, over the world. Although HCTZ is known to be photosensitizing, the mechanisms involved in its potential prophotocarcinogenic effects remain unclear. Under acute exposure, therapeutically relevant concentrations of HCTZ (70, 140, and 370 ng/mL) amplified UVA-induced double-strand breaks, oxidative DNA, and protein damage in HaCaT human keratinocytes, and this effect was associated to a defective activity of the DNA repair enzyme, OGG1. Oxidative damage to DNA, but not that to proteins, was reversible within few hours. After chronic, combined exposure to HCTZ (70 ng/mL) and UVA (10 J/cm 2 ), for 9 weeks, keratinocytes acquired a dysplastic-like phenotype characterized by a multilayered morphology and alterations in cell size, shape, and contacts. At the ultrastructural level, several atypical and enlarged nuclei and evident nucleoli were also observed. These transformed keratinocytes were apoptosis resistant, exhibited enhanced clonogenicity capacity, increased DNA damage and inflammation, defective DNA repair ability, and increased expression of the oncogene Δ Np63 α and intranuclear β -catenin accumulation (a hallmark of Wnt pathway activation), compared to those treated with UVA alone. None of these molecular, morphological, or functional effects were observed in cells treated with HCTZ alone. All these features resemble in part those of preneoplastic lesions and NMSCs and provide evidence of a biological plausibility for the association among exposure to UVA, use of HCTZ, and increased risk of NMSCs. These results are of translational relevance since we used environmentally relevant UVA doses and tested HCTZ at concentrations that reflect the plasma levels of doses used in clinical practice. This study also highlights that drug safety data should be followed by experimental evaluations to clarify the mechanistic aspects of adverse events.